Trends in attention deficit hyperactivity disorder drugs consumption, Israel, 2005–2012. (7th March 2014) - Ponizovsky, Alexander M.; Marom, Eli; Fitoussi, Israel
ABSTRACT Purpose The aim of this study was to describe trends in attention deficit hyperactivity disorder (ADHD) drugs consumption in Israel (Ritalin, Concerta, Daytrana, Vyvanse, Focalin, and Adderall) over the 8 years, 2005–2012, and to explore explanations for changes in amounts and patterns of the utilization. Methods Data for the period from 2005 to 2012 were extracted from the database maintained by the Israel Ministry of Health's Pharmaceutical Administration. The data were converted into a defined daily dose (DDD) per 1000 inhabitants per day. Results Consumption of all ADHD drugs covered by Israel's national health care system doubled over the study period, from 4.02 DDD/1000 inhabitants/day in 2005 to 9.92 DDD/1000 inhabitants/day in 2012. This rise was largely due to a fivefold increase in Concerta consumption (from 0.46 DDD/1000 inhabitants/day in 2005 to 2.28 DDD/1000 inhabitants/day in 2012) and a threefold increase in Ritalin consumption (from 1.43 DDD/1000 inhabitants/day in 2005 to 4.84 DDD/1000 inhabitants/day in 2012). Adderall (amphetamine mixed salts) consumption rose by 30% for the same period. A substantial trend was noted for increased utilization of high‐dose formulations together with proportional decline in low‐dose consumption. In the same period, cost of the medications has been reduced an average by 20–25%. Conclusions There has been a drastic rise in ADHD drugs consumption in Israel over 2005–2012. This has been associated with substantial reduction in cost and changes in the pattern of prescribing that characterized by increased prescription of high‐dose long‐acting preparations of ADHD drugs and decreased prescription of their low‐dose, short‐acting formulations. Copyright © 2014 John Wiley & Sons, Ltd.